Pesticide Exposure and Hypertension Risk in Indonesian Agricultural Workers: A Systematic Review and Meta-Analysis - Suratman; Ali, Khaidar; Rizaldi, Muhammad Addin (Universitas Airlangga, 2025)
Introduction: Agriculture workers exposed to pesticides are at high risk for hypertension, which is known as a cause of cardiovascular disease worldwide. Due to agricultural relevance and pesticides exposure, pesticide use and hypertension have garnered attention. This study investigated pesticide exposure and hypertension risk. Discussion: In line with the PRISMA guidelines, we conducted a systematic review and meta-analysis of cross-sectional studies published between 2015 and 2024. A total of 14 studies from Indonesia focusing on agriculture were selected, representing a variety of geographic areas and research methods. The pooled analysis revealed a prevalence ratio (PR) of 1.64 (95% CI: 1.35–1.99), indicating that farmers exposed to pesticides had a far higher risk of hypertension than those who were not. Long-term exposure, higher doses of pesticides containing active ingredients of commonly used pesticides, such as chlorpyrifos and profenofos, frequent spraying, improper use of personal protective equipment (PPE), age, smoking, and work-related stress all increased risk. Pesticides can affect cardiovascular control through oxidative stress, neuroendocrine disruption, and endocrine disruption, according to global reports. Conclusion: This systematic review and meta-analysis underscores the significant environmental health risks posed by pesticides exposure, particularly its contribution to hypertension among Indonesian agriculture workers. Prolonged exposure, inadequate use of PPE, and poor safety practices exacerbate these risks. The findings highlight the urgent need for stricter environmental health regulations, the implementation of integrated pest management, and improved education on pesticide safety. These measures are essential to protect agricultural workers and reduce pesticide-related health risks in communities.